2018
DOI: 10.2337/db17-1280
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Reduces β-Cell Oxidative Stress by Linking Autophagy With the Antioxidant Response

Abstract: Production of reactive oxygen species (ROS) is a key instigator of β-cell dysfunction in diabetes. The pleiotropic cytokine interleukin 6 (IL-6) has previously been linked to β-cell autophagy but has not been studied in the context of β-cell antioxidant response. We used a combination of animal models of diabetes and analysis of cultured human islets and rodent β-cells to study how IL-6 influences antioxidant response. We show that IL-6 couples autophagy to antioxidant response and thereby reduces ROS in β-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 50 publications
2
53
0
1
Order By: Relevance
“…The acute phase pro-inflammatory cytokine IL-6 has pleiotropic effects with the ability to promote inflammation and angiogenesis upon pathologic conditions, but it has also shown to be protective in the neural retina [36][37][38]. It has been shown that IL-6 linked autophagy to antioxidative response, and reduced oxidative stress via p62/SQSTM1 and nuclear factor erythroid 2-related factor 2 (NRF2) [39][40][41]. In our previous study, Resvega induced autophagic flux upon declined proteasomal degradation [22].…”
Section: Discussionmentioning
confidence: 99%
“…The acute phase pro-inflammatory cytokine IL-6 has pleiotropic effects with the ability to promote inflammation and angiogenesis upon pathologic conditions, but it has also shown to be protective in the neural retina [36][37][38]. It has been shown that IL-6 linked autophagy to antioxidative response, and reduced oxidative stress via p62/SQSTM1 and nuclear factor erythroid 2-related factor 2 (NRF2) [39][40][41]. In our previous study, Resvega induced autophagic flux upon declined proteasomal degradation [22].…”
Section: Discussionmentioning
confidence: 99%
“…These results supported recent studies, suggesting that the upregulation of HO-1 alleviated H 2 O 2 -induced ROS and oxidative injury in HepG2 cells [49,50], although, in this study, we did not determine whether ectopic HO-1 overexpression inhibited the apoptosis of hepatoma cells. Since a recent study indicated that IL-6 drives ROS reduction by increasing Nrf 2, a transcription activator of the HO-1 gene, expression in human islet β-cells [51], further investigations into the role of IL-6-HO-1 crosstalk in hepatoma cells, in terms of ROS synthesis, are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, IL‐6 plays an important role in regulating metabolism, particularly glucose homoeostasis . IL‐6 has been identified as a cytoprotective molecule in inflammatory disorders, as shown in multiple pre‐clinical trials of organ transplantation, and therefore may have potential applications in clinical islet transplantation as a novel therapeutic molecule. On the other hand, IL‐6 is regarded as an inflammatory factor and an important indicator in the field of xenotransplantation .…”
Section: Discussionmentioning
confidence: 99%